Chinese equestrian policy development: a narrative review - Li, Jiaxin; Sánchez-García, Raúl (Frontiers in Veterinary Science, 2024)
Introduction This paper provides an overview of the Chinese equestrian policy documents and regulations from 1978 to 2022. While the horse business is shifting from traditional to leisure and sport pattern in China, through the analysis of the policies and regulations. Objectives This paper aims to provide a concise overview of the government's policies which growth of equestrian sports in China over the past four decades (since 1978). Method Under the guidance of Whitemore and Knafl's 5-step approach to policy analysis, a systematic analysis of policy content, context, and governance processes is conducted. As of 2022, 29 documents from official and semi-official sources had been extracted, classified, and examined for records. Results and conclusion As of 2022, 29 documents from official and semi-official sources had been extracted, classified, and examined for records. The first is whether the policy is useful or not, its goals are vague and unclear. And there isn't much interaction between the areas it affects. Second, the policies are inconsistent and unstable. Third, there is a deficiency in terms of professional evaluation and relevancy. Fourth, pre-development preparation is not done due to the lack of an industry chain cycle. The complex causes of these issues include the sports management system, the government's policy ideals, and the competition of interests among policy stakeholders.